Strong fields. Some features of dynamics of particles and waves - Buts, V.A. (Вопросы атомной науки и техники, 2008)
Some most significant results, which were got at research of wave - particle type interaction and of wave - wave type interaction are briefly reported. Коротко викладені деякі найбільш важливі результаты, які були здобуті при дослідженні процесу взаємодії типу хвиля-частинка та типу хвиля-хвиля. Кратко изложены некоторые наиболее важные результаты, полученные при исследовании взаимодействий типа волна-частица и типа волна-волна.